Answer:
The translation S(x, y) for the identity transformation, I = ST(x, y) is S(x, y) = ( x - 2, y + 5)
Explanation:
Identity transformation is the transformation that results in the copying of the source data to the destination data without change.
Given that T(x, y) = (x + 2, y + 5)
The identity transformation I = S(T(x, y)) that would allow a data (x, y) to remain the same at the destination after the transformation T(x, y) is given as follows;
Where S(x, y) = ( x - 2, y + 5), we have;
S(T(x, y)) = S(x + 2, y + 5) = (x + 2 - 2, y + 5 - 5) = (x, y)
Therefore the translation S(x, y) that would yield the identity transformation, I = ST(x, y) is S(x, y) = ( x - 2, y + 5).